Is culture reflected in transliteration? Transliteration of Chinese street food names in Malaysia - Zhu, Hongxiang; Ang, Lay Hoon (SAGE Publications, 2025)
Street foods in Malaysia, which are enjoyed by a variety of ethnic groups, provide insights into the country’s sociocultural reality. However, relatively few studies have explored the street food names from a translation perspective. Drawing on a sociolinguistic approach, this study examines the transliteration of street food names from Chinese to Romanized languages in Malaysia and explores the reflection of cultures in transliterations. A purposive sampling method was used in Kuala Lumpur to collect the data. A total of 792 street food names with transliterations were analyzed—including rice, noodles, and others. A qualitative analysis was used to analyze the transliterations of street food names. The cultures were identified by the pronunciations in transliterations and verified by Chinese Malaysians who speak both Chinese dialects and Malay. The results revealed that there were different syllable-to-syllable spellings, alphabetic variants, capital or small letters, and various pronunciations based on Chinese dialects rather than Chinese Pinyin. The transliterations were based on Cantonese, Hokkien, Malay, Hakka, Japanese, Teochew, Indonesian, Thai, and Korean pronunciations. In conclusion, the transliterations of street food names in Malaysia reflect the different cultures of the Chinese clans, the local Malay, and overseas cultures—especially east and southeast Asian ones.